(untitled) (Comprehensive Journal of Science, 2026)
A descriptive cross-sectional study was conducted on 270 dentists and dental technicians currently working in the cities of Tripoli, Nalut and Ajaylat, of whom only 150 technicians and dentists responded, A questionnaire form was prepared for the research consisting of 29 multiple-choice questions with answers for the flexible denture, the acrylic denture or both, including two dentures "flexible denture and acrylic denture" were prepared in cooperation with the Rixos Laboratory in the city of Tripoli; To conduct experiments on the content of the research objectives, the result was 87 (58%) dental technicians, and 63 (42%( dentists, while the result was that most of the respondents work in dental practice, and have more than eight years of experience at a rate of (48.67%) and their number is 73, and we find that the flexible denture is the most stable in the patient’s mouth at a rate of (56%) at a rate of 84, and the best in terms of aesthetics at a rate of (53.3%) and their number is 80, and thus we find that the acrylic denture changes color quickly at a rate of (34%) at a rate of 51, and it is the denture suitable for the elderly at a rate of (46%( at a rate of 69, and this study concluded that the flexible denture has better flexibility and transparency than the traditional acrylic denture, while the traditional acrylic denture has hardness and strength, as although flexible dentures are not taught in Libyan dental universities, more than a third of the respondents prefer this treatment and recommend it to their patients, taking into account the disadvantages and advantages, as it is clear from this research that technicians Dentists are more satisfied with flexible RPD than with acrylic dentures.